2017
DOI: 10.4103/0974-2727.199637
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm colonization in chronic treatment refractory infections presenting with discharging sinuses: A study in a tertiary care hospital of Eastern India

Abstract: INTRODUCTION:Treatment refractory chronic recurrent infections mean those chronic infections which recur by same causal agents with similar drug responsiveness after apparent relief following full course of recommended antimicrobial management.MATERIALS AND METHODS:Fifty different samples were collected from patients with chronic surgical site infections, laparoscopic port site infections, anal fistula, mesh hernioplasty, chronic dacryocystitis, chronic osteomyelitis, and chronic burn wounds. Samples were proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The rate of biofilm-forming multi-drug resistant P. aeruginosa is increasing in India and the developing antibiotic-resistant biofilm forming P. aeruginosa is worrisome [14]. Recent studies showed that biofilm producing P. aeruginosa isolated from clinical samples were resistant to amikacin, imipenem, ciprofloxacin and gentamicin [14][15][16]. This study found that out of 24 strains of P. aeruginosa studied, 16 were biofilm producers and most of the biofilm forming strains were resistant to gentamicin and ciprofloxacin.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of biofilm-forming multi-drug resistant P. aeruginosa is increasing in India and the developing antibiotic-resistant biofilm forming P. aeruginosa is worrisome [14]. Recent studies showed that biofilm producing P. aeruginosa isolated from clinical samples were resistant to amikacin, imipenem, ciprofloxacin and gentamicin [14][15][16]. This study found that out of 24 strains of P. aeruginosa studied, 16 were biofilm producers and most of the biofilm forming strains were resistant to gentamicin and ciprofloxacin.…”
Section: Discussionmentioning
confidence: 99%
“…There were 30 studies conducted in Asian countries that discussed the microbiology of wound infections and the prevalence of P. aeruginosa ( Figure 1 ). Countries that were represented in the literature search included China [ 69 , 70 , 71 ], India [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ], Indonesia [ 83 , 84 ], Iran [ 85 , 86 ], Kuwait [ 87 ], Lebanon [ 88 ], Malaysia [ 89 , 90 , 91 ], Pakistan [ 92 , 93 , 94 ], Singapore [ 95 ], Turkey [ 96 ], and Iraq [ 97 ]. Most of the included studies focused on diabetic foot infections, and the frequency of P. aeruginosa isolation was therefore comparable when all chronic wound infections were evaluated or if diabetic foot infections specifically were analyzed ( Figure 1 and Figure 2 ).…”
Section: Prevalence Of P Aeruginosa In Wound Infec...mentioning
confidence: 99%
“…Contrary to the rest of the continent, P. aeruginosa was the most abundant pathogen in India and Malaysia. Of the 11 studies that took place in India, five of the investigations found that P. aeruginosa was the most commonly isolated organism, which was followed by S. aureus and members of the order Enterobacterales (mainly Escherichia coli and Klebsiella pneumoniae ), respectively [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. The reported frequency of P. aeruginosa isolation was also relatively consistent with a range of 16–30% in every Indian study.…”
Section: Prevalence Of P Aeruginosa In Wound Infec...mentioning
confidence: 99%
See 1 more Smart Citation
“…AFM was also used to detect biofilms formed by anaerobes and atypical mycobacteria isolated from hospital patients [ 139 ]. Recently, nanoresolution of the atomic force microscope and AFM-based morphological analysis was also reported to be useful in investigation of K. pneumoanie biofilms, notably by combining AFM with infrared (IR) spectroscopy and spectral imaging, which, overall, allowed for the collection of data on the composition and distribution of the chemical components of biofilm [ 140 ].…”
Section: Afm-based Investigation As a Novel Approach To Fight Withmentioning
confidence: 99%